2018
DOI: 10.1152/ajpregu.00412.2017
|View full text |Cite
|
Sign up to set email alerts
|

Differential influence of vitamin C on the peripheral and cerebral circulation after diving and exposure to hyperoxia

Abstract: We examined if the diving-induced vascular changes in the peripheral and cerebral circulation could be prevented by oral antioxidant supplementation. Fourteen divers performed a single scuba dive to eighteen meter sea water for 47 min. Twelve of the divers participated in a follow-up study involving breathing 60% of oxygen at ambient pressure for 47 min. Before both studies, participants ingested vitamin C (2 g/day) or a placebo capsule for 6 days. After a 2-wk washout, the study was repeated with the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…The approximately 10% increase in PCAv observed in the current study is consistent with the 8-10% elevation in PCAv reported in two separate studies by Barak et al (2016Barak et al ( , 2018 following a single SCUBA dive with the same dive profile; that is, 18 m sea water with a 47 min bottom time. Further, our data extend these findings and reveal subtle alterations in changes in extra-cranial blood flow patterns, including vasodilatation and reductions in shear rate.…”
Section: Cerebrovascular Regulation At Rest Following a Scuba Divesupporting
confidence: 91%
See 4 more Smart Citations
“…The approximately 10% increase in PCAv observed in the current study is consistent with the 8-10% elevation in PCAv reported in two separate studies by Barak et al (2016Barak et al ( , 2018 following a single SCUBA dive with the same dive profile; that is, 18 m sea water with a 47 min bottom time. Further, our data extend these findings and reveal subtle alterations in changes in extra-cranial blood flow patterns, including vasodilatation and reductions in shear rate.…”
Section: Cerebrovascular Regulation At Rest Following a Scuba Divesupporting
confidence: 91%
“…The increases in intra-cranial CBV are perhaps explained by hyperoxiainduced cerebral vasoconstriction due to (1) compensatory increases in respiration and resultant reductions in P CO 2 (Eldridge & Kiley, 1987); and/or (2) increased reactive oxygen species (ROS) (Modun et al, 2012;Obad et al, 2010) and related reductions in nitric oxide bioavailability (Theunissen et al, 2013) and cerebral metabolism (Mattos et al, 2019); and such changes are reflected in additional stresses of diving (e.g. high hydrostatic pressure, water temperature, exercise) independent of hyperoxia per se (Barak et al, 2018). Indeed, the previously reported transient elevations in CBV observed 30 min following a single SCUBA dive were acutely restored by 60 min post-dive (Barak et al, 2016(Barak et al, , 2018; such increases in CBV were suppressed with antioxidant administration and were not apparent during exposure to matched duration 60% O 2 breathing experienced during the dive (Barak et al, 2018).…”
Section: Cerebrovascular Regulation At Rest Following a Scuba Divementioning
confidence: 99%
See 3 more Smart Citations